The Effect of Work Motivation and Discipline on Employee Performance: Study at a Convection Service Company in the City of Bandung - Ella Klodiya Pandia; Vicky Achmad Zulfikar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The primary objective of this study is to investigate and assess the impact of motivation on employee performance, the effect of work discipline on employee performance, and the combined influence of motivation and work discipline on employee performance within a convection services company located in Bandung. The employed research methodology is descriptive and verificatory in nature. The study's population comprises employees from a single convection services company in Bandung. The sample size for this study was determined to be 137 respondents, utilizing the Slovin technique. The data collection process involved the administration of questionnaires, while data analysis was conducted using path analysis with the aid of SPSS 21 for Windows. Based on the statistical analysis results, it is evident that Motivation (X1) exhibits a direct influence of 28.9%, an indirect influence via competence (X2) of 15.3%, and an overall influence of 44.3%. The Work Discipline (X2) variable exhibits a direct influence of 12.5% and an indirect influence through Motivation (X1) of 15.3%, resulting in a cumulative influence of 27.8%. The coefficient of determination (R2), represented as a percentage, indicates that the collective impact of all the independent variables, precisely Motivation (X1) and Work Discipline (X2), on the dependent variable, employee performance, amounts to 0.722 or 72.2%. In addition, it should be noted that other unexplored variables may have an impact on performance, as evidenced by the value of ɛ = 0.278, equivalent to 27.8%. Therefore, it can be inferred that motivation and work discipline positively and substantially impact employee performance within the convection services company located in Bandung.